The Use of AI in Education to Improve Elementary School Students' Learning Outcomes - Agustinus Sembiring; Theresia Herlina (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study examines the impact of Artificial Intelligence (AI) on learning quality in elementary schools with limited technology infrastructure. Addressing unequal AI adoption, a quasi-experimental design was applied to 130 fifth-grade students divided into AI-based and conventional groups. Data were collected through pretest–posttest and EKOP questionnaires, analyzed using t-tests and reliability measures. Results show the AI group improved from a mean pretest score of 56.65 to 78.85 (gain = 22.20), while the non-AI group increased from 57.15 to 67.60 (gain = 10.45), with significant differences (t = 15.15, p < 0.001). EKOP scores also favored the AI group across all indicators. This study contributes empirical evidence that AI enhances engagement, critical thinking, and learning outcomes in rural elementary contexts.